Graphene tweaking Hamaker constant of SiC nanoparticles: A new horizon to solve the conflict between strengthening and toughening. (June 2016) - Fadavi Boostani, A.; Tahamtan, S.; Yazdani, S.; Khosroshahi, R. Azari; Wei, D.; Sahamirad, H.; Zhang, X.M.; Jiang, Z.Y.
Abstract: This study reveals a promising feature of graphene encapsulating process to significantly enhance the mutually inclusive tensile strength and ductility of aluminium based composites using the semi-solid powder forming process. It was corroborated based on van der Waals–Casimir interaction free energy that graphene sheets have an unprecedented capacity to manipulate the Hamaker constant of SiC nanoparticles, prompting formation of nano/micro-sized grains. Authenticating by the strengthening model, fractographic observations have also demonstrated the unique functionality of graphene sheets in strengthening via grain refining, thermally enhanced dislocations, shear-lag, geometrically necessary dislocations, crack bridging and fibre pull out mechanisms. Graphical abstract: